Making the Curriculum Culturally Relevant: Relations between the Global and Local - Julia Preece (Adult Education Research Conference, 2000)
This paper analyses findings from action research which explored the impact of devising higher education curricula which are culturally and socially relevant to marginalised adult learners. The theoretical framework draws on the relationship between globalisation and local identity.